Analysis Of Facts or Circumstances That Are Proven Simply In The Context Of Proving Other Creditors In Bankruptcy Applications - Giacinta Nadima; Richard C. Adam (Jurnal Indonesia Sosial Teknologi, 2023)
In filing a bankruptcy petition, the petitioner must fulfill the requirements for the petition to be granted by the panel of judges. These requirements are stipulated in Article 2 paragraph (1) in conjunction with Article 8 paragraph (2) of Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. According to these requirements, the bankruptcy petitioner must provide evidence that there are other creditors, either by presenting these other creditors as witnesses or by the debtor's acknowledgment in the form of promissory notes or other documents. However, in its implementation, it turns out that the method of proving this is subject to multiple interpretations, leading to legal uncertainty, namely whether other creditors need to be present in the hearing or if the debtor's acknowledgment is sufficient. This research will be conducted using a normative research method, which involves studying legislation with an approach to bankruptcy cases in Indonesia